The electrical properties of boron-containing poly(vinyl alcohol) derived ceramic organic semiconductor - Yakuphanoğlu, Fahrettin; Schiavon, Marco Antnio (Wiley, 2008)
The direct and alternating current conductivity, space charge limited current, and thermoelectrical properties of boron-containing poly(vinyl alcohol)-derived ceramic have been investigated. The electrical conductivity of the sample increases with increase in temperature and the room temperature conductivity of the sample was found to be 3.82 x 10(-5) S/cm. The electrical conductivity and thermoelectric power results suggest that the PVAB polymer has p-type electrical conductivity. The current-voltage characteristics indicate that at higher voltages, the space charge limited conductivity mechanism is dominant in the PVAB sample. The electronic parameters such as the position of the Fermi level bottom of the conduction band, E-F, the density of states in conduction band N-c, effective mass of holes m, were found to be 0.44 eV, 2.12 x 10(25) m(-3), and 0.59 m(o), respectively. Alternating current conductivity results suggest that the correlated barrier hopping conductivity is dominant in AC conductivity mechanism of the sample. The imaginary part of the dielectrical modulus at different temperatures shows a relaxation peak, indicating a temperature-dependent non-Debye relaxation.
Keywords: Relaxation; Glasses